Education in Singapore: a look at certain issues in today's society - Lim, Bak Soong (2015)
The authors fully agree with the Senior Minister's belief that education has the ability to reshape and restructure the Singapore society in the interest of nation-building. Over the past 28 years since independence, education in Singapore has undergone several changes. The present education system is one that is geared towards providing at least ten years of general education for all children. The authors have identified three hot topics for discussion in this report which are of great interest to educationists, parents, students and the public at large. These three topics are Streaming, Competition and Tuition. Streaming was introduced into the Singapore education system in 1979 with the objective to minimise educational wastage and allow each child to learn at his own pace. As streaming caters to the different learning aptitudes of students, it is still being implemented presently. A field study in the form of a survey with teachers and students was conducted to gather their feedback on the effects of and problems with streaming. Finally, the authors provide some solutions to the problems identified. Intense competition amongst schools and students has emerged as a major aspect in our education system. The authors acknowledge that there are certain demerits to having a competitive school environment. However, it is not good either to have a system where competition does not exist at all. The important thing is to achieve a balance such that competition does not reach an extent whereby it will cause antagonism amongst competitors and disrupt learning. Interviews were carried out to find out what are the strategies that are adopted by schools to remain competitive. We will also look at the effects of excessive competition, with suggestions to cope with or reduce pressure. The trend for students to receive private tuition is getting more common now than ever before. This raised questions such as "Are the schools not teaching enough?" and "Have the parents lost faith in the education system ?" A field study was conducted to gather the reasons, trends and effects of tuition and the authors also recommend guidelines to aid parents in choosing the appropriate tuition centre and tutor. In addition, the importance of the present education system to our society will be discussed. The authors critically analyse how well our education system meets the society's needs. Last but not least, the ideal education system envisioned by the authors is presented. Such an education system should nurture a child's cultural and aesthetic qualities, physical development, and lead to the building of character and strong moral values.